Pengaruh Kecerdasan Emosional Terhadap Kinerja Karyawan Melalui Organizational Citizenship Behaviour (OCB) Di PT. Asia Tritunggal Jaya Cihideung - Hidayat, Ujang Rahmat; Karmila, Mila; Barlian, Barin (Utami Publisher, 2024)
The purpose of this research is to determine and analyze the influence of emotional intelligence through organizational citizenship behavior (OCB) on employee performance in the sales clerk section at PT. Asia Tritunggal Jaya Cihideung. The research method used is a survey method, data obtained directly through questionnaires to 80 respondents taken from all employees in the sales clerk section at PT. Asia Tritunggal Jaya Cihideung. Sampling uses saturated samples. The analytical methods used in this research are path analysis and Sobel tests. Based on the research results, it shows that emotional intelligence has a significant effect on organizational citizenship behavior (OCB), emotional intelligence and organizational citizenship behavior (OCB) have a significant effect on employee performance and organizational citizenship behavior (OCB) is unable to become an intervening variable between emotional intelligence and employee performance.